FEATURES OF DESIGN OF ADAPTIVE MULTIFUNCTIONAL HEADWEAR - BALAKLAVA - LUSHCHEVSKA, Olena; BUKHANTSOVA, Liudmyla; DITKOVSKA, Olesya; YANTSALOVSKYI, Oleksandr (Herald of Khmelnytskyi National University. Technical sciences, 2022)
The paper presents the results of information research on modern adaptive multifunctional clothing. In addition to the main functions, these clothes have additional functions that expand their purpose. The design of such products aims to improve the efficiency of human adaptation to specific conditions through a multifunctional system, clothing. This process requires integrating research into comfort, functionality, and protective properties of materials and clothing, including environmental protection and fashion sustainability. The classification of adaptive multifunctional clothes by functionality, usefulness, type of transformation, type of means of influence, and duration of impact is developed. It is proposed to expand the functionality of the balaclava headdress by giving it therapeutic and prophylactic properties. The product will positively affect the human body by affecting the biologically active areas on the head and neck. Based on the analysis of existing balaclavas, their classifier was developed. The most widespread constructive and technological decisions of such products are defined. It is established that modern balaclavas are designed mainly in the unisex style. Their design often consists of three parts, which gives the product high ergonomic comfort and the possibility of transformation.